The Impact of Earplugs and Eye Masks on Sleep Quality in Surgical ICU Patients at Risk for Frequent Awakenings. Issue 9 (September 2021) - Obanor, Osamudiamen O.; McBroom, Mandy M.; Elia, Jennifer M.; Ahmed, Farzin; Sasaki, Jun D.; Murphy, Kelly M.; Chalk, Shannon; Menard, Gloria A.; Pratt, Nadia V.; Venkatachalam, Aardhra M.; Romito, Bryan T.
Abstract : OBJECTIVES: Sleep disturbances may contribute to the development of delirium, prolonged ICU stay, and increased mortality. There is conflicting data on the effectiveness of earplugs and eye masks for sleep promotion in the ICU. This study evaluates the impact of earplugs and eye masks on sleep quality in postoperative surgical ICU patients at risk for frequent awakenings. DESIGN: Prospective randomized controlled trial. SETTING: Surgical ICU within the University of Texas Southwestern Medical Center. PATIENTS: Adult, female patients admitted to the surgical ICU requiring hourly postoperative assessments following breast free flap surgery between February 2018 and October 2019. INTERVENTIONS: Patients were randomized into an intervention group or a control group. The intervention group received earplugs and eye masks in addition to standard postoperative care, whereas the control group received standard postoperative care. MEASUREMENTS AND MAIN RESULTS: The primary outcome was overall sleep quality assessed via the Richards-Campbell Sleep Questionnaire. Secondary outcomes of patient satisfaction and rates of ICU delirium were assessed with a modified version of the Family Satisfaction in the ICU survey and the Confusion Assessment Method for the ICU. After a planned interim analysis, the study was stopped early because prespecified criteria for significance were attained. Compared with the control group's average Richards-Campbell Sleep Questionnaire total score of 47.3 (95% CI, 40.8–53.8), the intervention group's average Richards-Campbell Sleep Questionnaire total score was significantly higher at 64.5 (95% CI, 58.3–70.7; p = 0.0007). There were no significant between-group differences for Confusion Assessment Method for the ICU scores or modified Family Satisfaction in the ICU survey scores. CONCLUSIONS: These results suggest that earplugs and eye masks are effective in improving sleep quality in ICU patients undergoing frequent assessments. The results strengthen the evidence for nonpharmacologic sleep-promoting adjuncts in the ICU.